CHOP Regulates Endoplasmic Reticulum Stress-Mediated Hepatoxicity Induced by Monocrotaline - Guo, Yazhou; Yang, Chen; Guo, Rong; Huang, Ruijie; Su, Yongxia; Wang, Shuai; Kong, Yezi; Wang, Jianguo; Tan, Chengjian; Mo, Chonghui; Wu, Chenchen; Zhao, Baoyu (Frontiers in Pharmacology, 2021)
Monocrotaline (MCT), one of pyrrolizidine alkaloids, is the major toxin in Crotalaria, which causes cell apoptosis in humans and animals. It has been reported that livers are the vulnerable target of MCT. However, the exact molecular mechanism of the interaction between endoplasmic reticulum (ER) stress and livers injury induced by MCT is still incompletely clearly. In this study, the cytotoxicity of MCT on primary rat hepatocytes was analysis by CCK-8 assay and Annexin V-FITC/PI assay. Protein expression were detected by western blotting and immunofluorescence staining. As a result, MCT has significant decreased the cell viability and mediated apoptosis of primary rat hepatocytes. Meanwhile, MCT also could induce ER stress in hepatocytes, indicated by the expression of ER stress-related proteins, including GRP78, p-IRE1α, ATF6, p-eIF2α, ATF4 and CHOP. Pretreated with 4-PBA, an inhibitor of ER stress, or knockdown of CHOP by siRNA could partly enhance cell viability and relieve the apoptosis. Our findings indicate that demonstration of ER stress is involved in the hepatotoxicity induced by MCT, and CHOP plays an important role in this process.